The Use of Storyjumper in Teaching Descriptive Text Writing to EFL Students - Wersi Murtini, Ni Made (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2023)
Writing is one of the four language skills that EFL students must learn. Because writing is utilized in everyday communication, it plays a significant part in communication. The current study was mostly based on early observations of 25 subjects in Semester 1B of the English Language Education Study Program's IEC class, which revealed that the majority of the subjects’ writing skills remained low. Furthermore, the current study sought to determine whether or whether the writing skills of first-semester students in the English Language Education Study Program's 1B class might be improved by the usage of Storyjumper. To attain the goal, the researcher conducted classroom action research in two cycles. Furthermore, the following study instruments were used to collect the necessary data: pre-test, post-test 1, post-test 2, and post-test 3. The data was then examined by comparing the pre-test and post-test results, which revealed significant improvements in the subjects' mean scores from pre-test to post-test. Based on the findings of the research instruments, it is possible to infer that the use of a Storyjumper can improve the writing skills of students in 1B of IEC Class of the English Language Education Study Program.